2021
DOI: 10.1186/s12876-021-01705-9
|View full text |Cite
|
Sign up to set email alerts
|

mRNA profiling of a well-differentiated G1 pancreatic NET correlates with immunohistochemistry profile: a case report

Abstract: Background Neuroendocrine neoplasms (NENs) are a complex group of tumours that occur in many organs. Routinely used IHC markers for NEN diagnosis include CgA, synaptophysin, Ki67 and CD56. These have limitations including lack of correlation to clinical outcomes and their presence in non-tumour tissue. Identification of additional markers and more quantitative analyses of tumour tissue has the potential to contribute to improved clinical outcomes. We used qRT-PCR to profile the expression level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(13 reference statements)
1
2
0
Order By: Relevance
“…mRNA levels of four markers, synaptophysin (G2), CD44 (G2), DAXX (G1, G2) and CK7 (G3) did not correlate with the protein expression. These data are consistent with our previous study comparing mRNA and protein markers in a G1 pancreatic NET sample which showed that CD44 and DAXX mRNA and protein levels in G1 did not correlate [ 24 ]. Poor correlation with some CD antigens like CD24 and CD44 has also been previously reported in prostrate cell types [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…mRNA levels of four markers, synaptophysin (G2), CD44 (G2), DAXX (G1, G2) and CK7 (G3) did not correlate with the protein expression. These data are consistent with our previous study comparing mRNA and protein markers in a G1 pancreatic NET sample which showed that CD44 and DAXX mRNA and protein levels in G1 did not correlate [ 24 ]. Poor correlation with some CD antigens like CD24 and CD44 has also been previously reported in prostrate cell types [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Twenty-seven markers that correlated with a range of tumour-associated characteristics that had been previously tested in a pancreatic tumour case study [ 24 ] were selected ( Table 4 ). These markers included indicators of a neuroendocrine origin, a category of markers associated with EMT including proliferation, stem cell phenotype, cell adhesion, differentiation and tumour suppression, a multifunctional category that included EMT-associated markers and a category of vascular markers indicating angiogenesis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation